Performance analysis of proposed hybrid air conditioning and humidification–dehumidification systems for energy saving and water production in hot and dry climatic regions. (15th May 2015) - Nada, S.A.; Elattar, H.F.; Fouda, A.
Highlights: Integrative air-conditioning (A/C) and humidification–dehumidification desalination systems are proposed. Effects of operating parameters on the proposed systems are investigated. System configurations that have the highest fresh water production rate, power saving and total cost saving are identified. Abstract: Performance of integrative air-conditioning (A/C) and humidification–dehumidification desalination systems proposed for hot and dry climatic regions is theoretically investigated. The proposed systems aim to energy saving and systems utilization in fresh water production. Four systems with evaporative cooler and heat recovery units located at different locations are proposed, analyzed and evaluated at different operating parameters (fresh air ratio, supply air temperature and outside air wet bulb temperature). Other two basic systems are used as reference systems in proposed systems assessment. Fresh water production rate, A/C cooling capacity, A/C electrical power consumption, saving in power consumptions and total cost saving (TCS) parameters are used for systems evaluations and comparisons. The results show that (i) the fresh water production rates of the proposed systems increase with increasing fresh air ratio, supply air temperature and outdoor wet bulb temperature, (ii) powers saving of the proposed systems increase with increasing fresh air ratio and supply air temperature and decreasing of the outdoor air wet bulb temperature, (iii) locating the evaporative cooling after the fresh air mixing remarkably increases water production rate, and (vi) incorporating heat recovery in the air conditioning systems with evaporative cooling may adversely affect both of the water production rate and the total cost saving of the system. Comparison study has been presented to identify systems configurations that have the highest fresh water production rate, highest power saving and highest total cost saving. Numerical correlations for fresh water production rate and total system energy consumption are developed and presented in terms of the controlling parameters.